DIVERSITY INDICES OF SELECTED MACROBENTHOS IN KARANJA CREEK (DISTRICT- RAIGAD), MAHARASHTRA, WEST COAST OF INDIA - Pawar, Prabhakar R.; Kulkarni, Balasaheb G. (Journal of Indian Fisheries Association, 2007)
The diversity indices can be used as a good measure fo:r studying the effectÂ of industrial pollution because industrial wastes and sewage almost always :reduceÂ the diversity of natural systems into which they a:re discharged. A measurement ofÂ diversity often provides a better index of pollution than a direct measurement ofÂ pollutants. The assessment of macrobenthos diversity with :respect to diversityÂ indices :reflects the marine population and habitat disturbance, and also serves as an important indicator of environmental conditions. The present study wasÂ designed to investigate the diversity indices of selected macrobenthos at twoÂ ecologically distinct locations on the Ka:ranj a c:reek (District - Raigad),Â Maha:rasht:ra, west coast of India. Results on various diversity indices like Index ofÂ Frequency (F) o:r Importance Probability (Pi), Index of Dominance (c), RarityÂ Index (R), Shannon’s Index of General Diversity (H1Â ), Ma:rgalers Richness IndexÂ (R1) and Evenness Index (e) did not va:ry significantly. This demonstrates that atÂ present, Ka:ranja c:reek ha:rbou:rs varied fo:rms of mac:robenthic communityÂ showing no effect of human disturbance, but in future, measures must be taken fo:r the protection and conservation ofmac:robenthic community of the c:reek. Keywords: Diversity indices, conservation, macrobenthos, container freightÂ stations, J awaha:rlal N eh:ru Po:rt Trust